The suffering of love in the poem "For more than I want" by Mariano Melgar Valdivieso - Chavez, Yenny (2019)
The purpose of this study was to analyze and understand the loving suffering in the poem "Por más que quiero" by Mariano Melgar Valdivieso from the perspective of discourse analysis. The method used was hermeneutics, for which phenomenology, structuralism and the study of signs were taken into account. The technique used for the study was the analysis of poetic discourse: textual, enunciative, semiotic and pragmatic dimension. The poem evidenced the poet's loving suffering, grief caused by the disdain of heartbreak, the impossibility of forgetting and the non-correspondence of feelings to the lyrical subject by the loved one.